Association of Hypoalbuminaemia with the Angiographic Severity of Coronary Artery Disease in Patients with Acute Coronary Syndrome - Parvez, Jubair Mahmud; Rahman, Md Afzalur; Islam, AKM Monwarul; Aziz, Mustafizul; Mamun, Al; Arefin, Md Minhaj; Azam, MG (University Heart Journal, 2022)
Introduction: Serum albumin as a biomarker of coronary artery disease (CAD) severity and mortality in patients with acute coronary syndrome (ACS) is presently a subject of growing interest. Evidences accumulated from the studies suggest a possible association between serum albumin and severity of CAD. Aim of the study: The aim of this study was to find the association between serum albumin level and severity of CAD in patients of ACS. Methods: The present cross-sectional analytical study was carried out in the Department of Cardiology, National Institute of Cardiovascular Diseases (NICVD), Dhaka, Bangladesh, over a period of 1 year from July 2017 to June 2018. A total of 104 ACS patients undergoing coronary angiogram in the above-mentioned hospital during the index hospitalization within the specified time-frame were included in the study. Result: None of the demographic characteristics and traditional risk factors for CAD except age was found to be associated with severity of CAD. Friesinger Score was significantly higher in patients with low serum albumin than that in patients with normal serum albumin (8.84 ± 3.71 vs. 6.38 ± 3.02, p<0.001). Leman Score was also significantly higher in in the former group than that in latter group (12.48 ± 8.44 vs. 8.50 ± 4.94 mm, p = 0.004).The risk of having severe CAD in patients with low serum albumin was 5.46(95% CI = 2.141 – 13.925) (p < 0.001) times higher in terms of Friesinger score and 2.58(95% CI = 1.097 – 6.083) (p = 0.03) times higher in terms of Leaman score than that in patients with normal serum albumin. Spearman’s correlation revealed that the two variables serum albumin and Friesinger score, exhibit a significantly inverse correlation (r = -0.323, p = 0.001). Serum albumin demonstrated a significantly inverse correlation with Leaman score (r = -0.254, p = 0.009). Conclusion: The study concluded that serum albumin concentration was significantly associated with the severity of coronary artery disease with low serum albumin carrying at least two-fold higher risk of having severe CAD, as measured by the Friesinger and Leaman score, in patients with ACS. University Heart Journal 2022; 18(1): 44-49